Transformation of Islamic Boarding Schools in Facing the Development of Education in the Society 5.0 Era - Choeroni, Choeroni; Anwar, Khoirul (Universitas Islam Sultan Agung, 2024)
This article discusses the transformation that occurs in Islamic boarding schools in welcoming the era of society 5.0. Classical Islamic boarding schools in essence still use old traditions in their implementation in various matters related to Islamic boarding schools. Meanwhile, the society 5.0 era requires pesantren to adjust new things that must be done so that pesantren institutions are not left behind with the times. For this reason, pesantren needs to transform in various things about pesantren in order to be able to adjust to existing developments. The research methodology in this study uses literature research using primary and secondary data taken from books and articles which are then analyzed to get conclusions. The conclusion of this study is that pesantren has transformed in several ways, namely first, Transformation of Islamic Boarding School Leadership. Second, transformation of the pesantren education system. Third institutional transformation in Islamic boarding schools. Fourthtransformation Islamic boarding school curriculum. and the fifth, transformation Islamic boarding school education methods.